Persistent medication-induced neural adaptations, descending facilitation, and medication overuse headache - De Felice, Milena (Curr Opin Neurol, 2011)
PURPOSE OF REVIEW: An impediment to the investigation of mechanisms that drive headache is the inability of preclinical models to measure headache. Migraine attacks are associated with the development of cutaneous allodynia in some patients. Such cutaneous allodynia suggests a state of ‘central sensitization’ of pain transmission pathways and may additionally reflect the engagement of descending facilitation from pain modulatory circuits. For this reason, cutaneous allodynia has been measured in animal models as a surrogate of marker that may be relevant to headache. Overuse of antimigraine medications can promote an increase in the frequency and intensity of headache, a syndrome termed medication overuse headache (MOH). The mechanisms leading to MOH are not known, but may involve the processes of amplification including central sensitization and descending facilitation. This review explores potential mechanistic insights that have emerged from such studies and that could contribute to MOH. RECENT FINDINGS: Development of MOH has been recently associated with long-lasting adaptive changes that occur within the peripheral and central nervous systems. Preclinical studies have shown that repeated or continuous treatment with antimigraine drugs result in persistent upregulation of neurotransmitters within the orofacial division of the trigeminal ganglia and in development of cutaneous allodynia in response to migraine triggers, even weeks after discontinuation of the antimigraine drug. Additionally, descending facilitation is critical for the expression of cutaneous allodynia and may mask the expression of diffuse noxious inhibitory controls. SUMMARY: Medication-induced persistent pronociceptive adaptations might be responsible for lowering the threshold and amplifying the response to migraine triggers leading to increased frequency of headache attacks.